The basement morphology under Tongariro National Park, southern Taupo Volcanic Zone. Issue 4 (2nd October 2018) - Robertson, Edwin I.; Davey, Frederick J.
ABSTRACT: Gravity data recorded across Tongariro National Park during the 1950s and 1960s are interpreted in terms of the morphology of the basement underlying the younger surficial sediments and volcanics. The gravity data were processed to Bouguer anomalies at a height of 500 m (the average elevation of the survey region). These anomalies were then separated into regional and residual anomalies after deriving a smoothly varying regional anomaly based on observed values at stations on greywacke outcrops in the region. Density-depth relations for sediments were derived from measured values in boreholes. Simple 2D gravity models using these density relationships were used to derive a 3D structural model for the region. The final model shows a deep asymmetric trough with a steep eastern margin running from the south end of Lake Taupo (2.5 km deep) and under Mt Tongariro (1 km deep) before fading away as a major feature near Mt Ruapehu.